EFEKTIFITAS MODA TRANSPORTASI BUS RAPID TRANSIT (BRT) DALAM MENUNJANG AKTIFITAS BEKERJA DI KOTA SEMARANG - Safitri, Octafiani; Bagus Prakoso, Surya; Irawati, Iin; Intan Pratiwi, Yesina (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
Transportation is the lifeblood of everyday life and one of the basic needs of society. Almost everyone needs transportation to meet their needs, such as the need for work, school, recreation and social interaction. The choice of transportation modes in an urban area is now increasingly varied, starting from private or public transportation. Various activities such as government administrative centers, communication centers, industrial centers and trade centers located in the city of Semarang are factors in all people's choices in using modes of transportation. This analysis uses AHP analysis by presenting it in the form of numbers, graphs, tables and narratives. AHP is a method used to rank decision alternatives and to choose the best of several criteria. AHP develops a numerical value to rank each decision alternative, which is based on how far each alternative meets the criteria of the respondent. Based on the data, it can be explained that the most important criteria for respondents to the choice of transportation mode are the time criteria of 96.78%, then the cost criteria of 2.90%, the next for the age criteria of 0.21% and the last for the criteria worker characteristics of 0.01%. Furthermore, the order of priority for selecting the first working mode of transportation is motorbikes at 91.41%, the second is BRT at 8.01% and the last is Angkot at 0.48%. This study concluded that based on the results and discussion of this study are as follows: Based on calculations AHP data processing can be explained that the most important criteria for respondents to the selection of work transportation modes are time criteria of 96.78%, then cost criteria of 2.90%, next for age criteria of 0.21% and finally for characteristic criteria workers by 0.01%. After obtaining the results of alternative weights, the priority for choosing the first working mode of transportation is motorbikes at 91.41%, the second is BRT at 8.01% and the last is Angkot at 0.48%.